Construction Supply Chain Management Implementation in Libyan Construction Industry - Elferghani, Almahdi M. A. (Eastern Mediterranean University EMU, 2017)
Researchers in construction management field have recently highlighted the importance of adopting the philosophy of supply chain management SCM in construction industry sector. The main driver behind considering this philosophy in construction sector was its remarkable successes within other industry sectors such as manufacture industry sector, wherein it was originally appeared. A construction project supply chain CSCM can be introduced as a systematic network includes material suppliers, manufacturing process, contractors and clients. These parties linking together through a flows of materials, data and cash. Therefore, the quality of communication, collaboration and sharing information between contractor companies, their suppliers and clients, determine the degree of achievement of within supply chain process. This research study presents understanding and analyzing of supply chain management SCM in Libyan construction industry LCI with emphasizing on the importance of relationship among construction supply chain parties including suppliers, contractors and clients along with the effects of SCM implementation on construction performance as well as the significant barriers to CSCM integration in LCI. In this study, the relationship between Libyan construction companies and their supply chain parties (suppliers, contractors and clients) has been investigated by analyzing the importance of the most influential factors affecting the success in supply chain relationship. In addition, Well-known performance indicators were iv examined related to adversarial relationships, adding value and developing reliability and information sharing within construction projects. This study intended to propose a conceptual framework for the implementation of SCM in LCI, for this purpose a questionnaire survey has been designed and distributed among Libyan construction companies randomly selected. A total of 62 responses have been collected for data analysis. Research results reveal that the trust, quality of materials provided and free flow of information among CSCM members impose considerable positive effects on successful relationship between supply chain parties. In addition, the long term and stable relationships are among the most significant factors to improve supply chain process, also inventory and storage considered to be critical functions affecting the efficiency of supply chain organization. Moreover, regarding to adopting SCM in construction performance the results indicates time predictability, effectiveness of communication systems and top management commitment are the most significant factors affecting CSCM performance. However, poor understanding of SCM concept is evaluated among the most significant barriers to integrate SCM conception in LCI. Keywords: Supply chain management, Construction supply chain management, Libya Construction Industry, Framework Model.

ÖZ: Yapım yönetimi alanındaki araştırmacılar, son zamanlarda inşaat sektöründe tedarik zinciri yönetimi (TZY) felsefesinin benimsenmesinin önemini vurgulamaktadırlar. Bu felsefeyi inşaat sektöründe değerlendiren başlıca etken, başlangıçta ortaya çıktığı imalat sanayii sektörü gibi diğer sanayi sektörlerinde de göze çarpan başarıydı.Bir inşaat projesi tedarik zinciri yönetimi (İTZY), malzeme tedarikçileri, üretim süreci, müteahhitler ve müşterileri içeren sistematik bir ağ olarak tanıtılır.Bu taraflar, bir dizi materyal, veri ve nakit yoluyla birbirine bağlıdır.Bu nedenle, yüklenici firmalar, tedarikçileri ve müşterileri arasındaki iletişim kalitesi, işbirliği ve paylaşım bilgileri tedarik zinciri sürecindeki başarı derecesini belirler. Bu araştırma, tedarikçi firmalar, yükleniciler ve müşteriler de dahil olmak üzere Libya inşaat sektöründe (LİS) inşaat tedarik zinciri tarafları arasındaki ilişkinin önemini vurgulayan TZY’nin anlaşılması ve analiz edilmesini,TZY uygulamasının inşaat performansı üzerindeki etkilerini ve İTZY entegrasyonunun önündeki en büyük engelleri anlatır.Bu çalışmada, tedarik zinciri ilişkisinde başarıyı etkileyen en etkili faktörlerin önemi analiz edilerek, Libya inşaat firmaları ile tedarik zinciri tarafları (tedarikçiler, müteahhitler ve müşteriler) arasındaki ilişki araştırılmıştır.Buna ek olarak, inşaat projelerinde karşılıklı ilişkiler, değer katma ve güvenilirlik geliştirme ve bilgi paylaşımı ile ilgili olarak iyi bilinen performans göstergeleriincelenmiştir.Bu çalışma, LİS'nde TZY'nin uygulanması için kavramsal bir çerçeve önerme amacındadır.Bu amaçla, rasgele seçilen Libya inşaat firmaları vi arasında bir anket hazırlanmış ve dağıtılmıştır.Veri analizi için toplam 62 yanıt toplanmıştır. Araştırma sonuçları, güven, sağlanan malzemelerin kalitesi ve İTZY üyeleri arasındaki serbest bilgi akışının tedarik zinciri tarafları arasındaki başarılı ilişkiye önemli derecede olumlu etkileri olduğunu ortaya koymaktadır.Buna ek olarak, uzun vadeli ve istikrarlı ilişkiler tedarik zinciri sürecini iyileştiren en önemli etkenler arasındadır. Ayrıca stok ve depolama, tedarik zinciri organizasyonunun verimliliğini etkileyen kritik işlevler olarak düşünülmektedir.Dahası, inşaat performansında TZY'ni benimsemekle birlikte, sonuçlar zaman öngörülebilirliğini, iletişim sistemlerinin etkinliğini ve üst yönetim taahhütünün İTZY performansını etkileyen en önemli faktörler olduğunugöstermektedir.Bununla birlikte, TZY konseptinin yetersiz bir şekilde anlaşılması, TZY kavramını LİS’ne entegre etmede en önemli engel olarak değerlendirilmektedir. Anahtar kelimeler: Tedarik Zinciri Yönetimi, İnşaat Tedarik Zinciri Yönetimi, Libya İnşaat Sektörü, Çerçeve Model.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assoc. Prof. Dr. İbrahim Yitmen
Keywords: Supply chain management; Construction supply chain management; Libya Construction Industry; Framework Model; Construction Industry - Supply Chain Management - Libya; Construction industry - Management; Construction projects - Project management